Research on the Us Electricity Market Based On Price Fluctuations. (June 2016) - Sun, Mei; Li, Juan; Gao, Cuixia; Han, Dun
Abstract: Electricity power is the basic industry and it plays an important role in the national economy. Based on the random matrix theory (RMT), we study the average correlations evolution of electricity price among 51 states, and identify their four regime shifts during the period of January 1990 to August 2014 in the U.S. residential, commercial and industrial electricity markets. Then, the genetic algorithm is applied to the analysis of clusters evolution. The results show that, the correlations of electricity price increased continually in the three departments. However, it decreased in 2012 which verifying the sensitivity to fuel market further. Besides, four regime shifts exist in the three departments even though the different time of occurrence caused by price level. Finally, the research results are analysed and summarized.